Evidence for the efficacy and safety of anti- interleukin-5 treatment in the management of refractory eosinophilic asthma - Xue, L; Hilvering, B; Pavord, I (SAGE Publications, 2015)
Two recent phase III trials in patients with severe eosinophilic asthma have shown that anti-interleukin 5 (IL-5) therapy with mepolizumab reduces the frequency of asthma attacks, improves symptoms and allows patients to reduce oral glucocorticoid use without loss of control of asthma. An earlier large 616 patient Dose Ranging Efficacy And safety with Mepolizumab in severe asthma (DREAM) study had shown that the only variables associated with treatment efficacy were a prior history of asthma attacks and the peripheral blood eosinophil count. The link between blood eosinophil counts and treatment efficacy is biologically obvious given that IL-5 has a pivotal role in eosinophil production, proliferation and chemotaxis. It is also clinically relevant as the blood eosinophil count is routinely measured and thus readily available in patients with asthma. Recognition of the link between airway or blood eosinophilia and treatment response was also important in the clinical testing of the alternative IL-5 blocker, such as reslizumab, which is currently being evaluated in a phase III randomized controlled trial (RCT) after having shown to improve lung function, improve symptom score and reduce sputum eosinophilia in a smaller phase IIb study. In addition, benralizumab, an IL-5α receptor blocker, has shown good effects in a phase IIb RCT with patients with severe asthma that had sputum eosinophilia and more recently in a phase IIa trial with patients with eosinophilic chronic obstructive pulmonary disease. Therefore anti-IL-5 treatment seems generally effective in eosinophilic asthma, either assessed by blood or airway eosinophilia. This factor together with the impressive clinical efficacy and good safety profile make anti-IL-5 (mepolizumab, reslizumab) and benralizumab (anti-IL-5 receptor α) very promising drugs for the treatment of patients with severe eosinophilic asthma, a subgroup that is in desperate need of better treatments.